Spiritual Well-Being in the Aftermath of Volcanic Eruption: An Interpretative Phenomenological Analysis of Survivors' Experiences in East Flores Indonesia - Irene Ataupah; Arthur Huwae (Universitas PGRI Yogyakarta, 2026)
Although the psychological impacts of natural disasters have been widely studied, in-depth research on the process of spiritual well-being formation among survivors of volcanic eruptions in eastern Indonesia, particularly within local cultural contexts, remains very limited. This study addresses this gap by exploring how survivors interpret and construct their spiritual well-being following the eruption of Mount Lewotobi Laki-Laki in East Flores. This study employed a qualitative design using Interpretative Phenomenological Analysis (IPA). Five survivors who directly experienced the eruption participated in in-depth semi-structured interviews. Data were analyzed using thematic analysis following Creswell’s procedural stages, including coding, theme development, and cross-case interpretation. The findings reveal that spiritual well-being develops through four interrelated domains: personal, communal, environmental, and transcendental. The personal domain involves self-acceptance and meaning-making; the communal domain emphasizes solidarity and mutual care; the environmental domain reflects renewed awareness of nature; and the transcendental domain highlights a deeper relationship with God. These domains are strengthened by mindfulness, self-compassion, and social support within the refugee community. This study contributes to the development of spiritual well-being theory in post-disaster contexts by providing an in-depth phenomenological understanding of survivors’ lived experiences. Practically, the findings suggest that community-based recovery programs should integrate spiritual and social dimensions to enhance holistic post-disaster rehabilitation. Keywords: disaster survivors, interpretative phenomenological analysis, spiritual well-being, volcanic eruption